Development of a PCR-RFLP method based on the transcription elongation factor 1-α gene to differentiate Fusarium graminearum from other species within the Fusarium graminearum species complex. (April 2018) - Garmendia, Gabriela; Umpierrez-Failache, Mariana; Ward, Todd J.; Vero, Silvana
Abstract: Fusarium head blight (FHB) is a destructive disease of cereals crops worldwide and a major food safety concern due to grain contamination with trichothecenes and other mycotoxins. Fusarium graminearum, a member of the Fusarium graminearum species complex (FGSC) is the dominant FHB pathogen in many parts of the world. However, a number of other Fusarium species, including other members of the FGSC, may also be present for example in Argentina, New Zealand, Ethiopia, Nepal, Unites States in cereals such as wheat and barley. Proper species identification is critical to research aimed at improving disease and mycotoxin control programs. Identification of Fusarium species is are often unreliable by traditional, as many species are morphologically cryptic. DNA sequence-based methods offer a reliable means of species identification, but can be expensive when applied to the analyses of population samples. To facilitate identification of the major causative agent of FHB, this work describes an easy and inexpensive method to differentiate F. graminearum from the remaining species within the FGSC and from the other common Fusarium species causing FHB in cereals. The developed method is based on a PCR-RFLP of the transcription elongation factor ( TEF 1-α ) gene using the restriction enzyme BsaH I. Highlights: PCR-RFLP of the TEF 1-α gene was developed for differentiation of F. graminearum from the remaining species within the FGSC. The PCR with Fg16F/R primers could be avoided. The developed method differentiate Fusarium graminearum from the other common Fusarium species causing FHB in cereals.